2020
DOI: 10.5796/electrochemistry.19-00059
|View full text |Cite
|
Sign up to set email alerts
|

A Spatially-Resolved <i>operando</i> High-Energy Confocal X-ray Diffraction Method for Observing Non-Uniform Degradation Phenomena in a Practical Cylindrical Lithium-ion Battery

Abstract: We report the results of spatially-resolved non-destructive operando electrode reaction analysis for practical cylindrical 18650 battery cells by using a high-energy confocal X-ray diffraction (XRD). A combination of highenergy X-rays (72 keV) and a confocal XRD method, which extracts structural information in a limited area that satisfies a confocal condition, allows us to observe electrode reactions in a cylindrical battery cell in a nondestructive way, resolving the double-side-coating electrode structure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The developed nondestructive imaging becomes one of the useful techniques for the sequential observations of resistance change during degradation; actual measurements of the cell-position-dependent resistive value require destructive analysis. 13) A nondestructive quantitative neutron Bragg-edge imaging of commercial fresh and fatigue prismatic LIB cells was performed on the negative electrode material (graphite). Bragg-edge fitting was performed using the graphite nonrandom crystalline-orientation evaluated in this work, and the column density images of C or Li atoms/ions for five crystalline phases were successfully obtained.…”
Section: / Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed nondestructive imaging becomes one of the useful techniques for the sequential observations of resistance change during degradation; actual measurements of the cell-position-dependent resistive value require destructive analysis. 13) A nondestructive quantitative neutron Bragg-edge imaging of commercial fresh and fatigue prismatic LIB cells was performed on the negative electrode material (graphite). Bragg-edge fitting was performed using the graphite nonrandom crystalline-orientation evaluated in this work, and the column density images of C or Li atoms/ions for five crystalline phases were successfully obtained.…”
Section: / Pmentioning
confidence: 99%
“…The LIB health status can be analyzed nondestructively by observing the changes in the crystal structure of the electrode materials via high-energy X-ray or neutron diffraction measurements. Baba et al 13) performed confocal high-energy X-ray diffraction measurements and revealed that the outer part of the positive electrode deteriorated more than the inner part in a deteriorated cell. Mühlbauer et al 14) performed neutron diffraction measurements and reported that the lithium distribution in the negative electrode in the charged state was nonuniform in the radial direction in a fatigued cell.…”
mentioning
confidence: 99%